2013
DOI: 10.1017/s0033822200048657
|View full text |Cite
|
Sign up to set email alerts
|

From an Estuary to a Freshwater Lake: A Paleo-Estuary Evolution in the Context of Holocene Sea-Level Fluctuations, SE Brazil

Abstract: ABSTRACT.A sediment core was studied to characterize the influences of Holocene sea-level variations in the Barra Seca River valley, in the Atlantic rainforest, Linhares, Espírito Santo, southeastern Brazil. Biological proxies (pollen, spores, and sponge spicules), 14 C dating, granulometry,  13 C,  15 N, C/N and major chemical elements revealed the establishment and the evolution of a paleo-estuary during the interval from ~7700-585 cal BP. During the interval ~7700-7000 cal BP, the study site was occupied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…This is proposed based on previous claims that RSL fall and increased sedimentary supply by river discharges, during the late Holocene, may have affected the relative position of the shoreline along the Brazilian coast, and, consequently, the characteristics of coastal stratigraphy and vegetation dynamics (Scheel-Ybert, 2000;Cohen et al, 2005a,b;Buso Junior et al, 2013;Guimarães et al, 2012;Smith et al, 2012;França et al, 2012;Cohen et al, 2012Cohen et al, , 2014.…”
Section: Climatic Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is proposed based on previous claims that RSL fall and increased sedimentary supply by river discharges, during the late Holocene, may have affected the relative position of the shoreline along the Brazilian coast, and, consequently, the characteristics of coastal stratigraphy and vegetation dynamics (Scheel-Ybert, 2000;Cohen et al, 2005a,b;Buso Junior et al, 2013;Guimarães et al, 2012;Smith et al, 2012;França et al, 2012;Cohen et al, 2012Cohen et al, , 2014.…”
Section: Climatic Changesmentioning
confidence: 99%
“…Climate changes and sea-level oscillations have caused significant impacts on coastal sedimentary dynamics and ecosystems along the Brazilian littoral during the late Quaternary (Suguio et al, 1985;Dominguez et al, 1992;Ledru et al, 1996;Angulo and Lessa, 1997;Behling et al, 1998b;Grimm et al, 2001;Bezerra et al, 2003;Martin et al, 2003;Cohen et al, 2005a,b;Angulo et al, 2006;Vedel et al, 2006;Behling et al, 2007;Sawakuchi et al, 2008;Lara and Cohen, 2009;Zular et al, 2013;Guimarães et al, 2012Guimarães et al, , 2013Buso Junior et al, 2013;França et al, 2012França et al, , 2013França et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…This was correlated with a larger continental input. Buso Junior et al (2013) also observed a change in the colonization areas that were previously flooded by swamp vegetation after 4396 cal yr BP. These data corroborate those of the present study where, after the possible marine regression, a high carbonized particle value at the top of the sediment core was observed and associated with the low frequency of ombrophilous forest elements and spores.…”
Section: Resultsmentioning
confidence: 91%
“…Trabalhos realizados na costa norte do estado do Espírito Santo (e.g. Buso Junior et al 2013b, França et al 2013, Castro et al 2013 utilizando isótopos estáveis (C e N) e bioindicadores, mostraram a presença de estuários e lagunas entre ~8000 e ~3000 anos AP na região, como resultado do aumento do nível relativo marinho (Angulo et al 2006). Ainda segundo esses autores, a litologia dos testemunhos sedimentares para o período era composta predominantemente por silte e argila, correspondendo assim a ambientes com características redutoras.…”
Section: Intervalo 1 (150 CM a 95 Cm; ~7589 Anos Cal Ap A ~5441 Anos unclassified